(untitled) (Revista Innova Educación, 2019)
This article presents a pedagogical experience for teaching a second language in a state public high school of mixed schooling, in this modality the students attend one day a week to attend face-to-face classes complementing the learning autonomously during the remaining days. The objective was to analyze the contribution of the inverted classroom as an English language teaching strategy. The study was descriptive quantitative with a quasi-experimental design, whose study variable is based on academic achievement in the subject of additional language to Spanish (English I) of a group of students who completed the first semester of a public baccalaureate in the mixed modality. In addition, an interview was held with the teacher in charge of the subject. The results obtained indicate 71% in the positive attitudes about the adoption of this didactic, which allowed the reinforcement of the topics of the course, as well as the favorable acceptance by the teacher in the use of this teaching methodology.